PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR IPS SISWA SMP NEGERI 4 BINAMU KABUPATEN JENEPONTO - Mustari, Mustari; Yahya, Muh.; Hakim, Maksud; Yunus, Muh. (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
This study aims to: (1) describe the utilization rate of school libraries in SMP Negeri 4 Binamu. (2) describes the level of student learning independence in SMP Negeri 4 Binamu. (3) to know the influence of school library utilization on IPS student achievement of SMP Negeri 4 Binamu. (4) to know the influence of learning independence on IPS student achievement of SMP Negeri 4 Binamu. (5) to know the influence of school library utilization and learning independence simultaneously on the achievement of IPS student learning SMP Negeri 4 Binamu Jeneponto District Lesson Year 2017/2018. The population in this study were all students of SMP Negeri 4 Binamu Jeneponto District Lessons Year 2017/2018 which amounted to 247 students and a sample of 37 students. The method used in this research is quantitative research with ex post facto approach. The first hypothesis test, second, using simple linear regression. The third hypothesis test uses multiple linear regressionBased on the data analysis, the research results show that: (1) The use of School Library of SMPN 4 Binamu students in the academic year 2017/2018 tends to be in good category with 89.18% (33 sample students) have utilized the school library well for the improvement of learning achievement . (2) Independence Learning of SMPN 4 Binamu students of the academic year 2017/2018 tend to be in good category with 78,38% (29 sample students) have undertaken self study activity. (3) There is influence of school library utilization to IPS student achievement of SMP Negeri 4 Binamu of Jeneponto Regency Lesson Year 2017/2018. (4) There is an influence of learning independence on learning achievement of IPS students of SMP Negeri 4 Binamu Jeneponto District Lesson Year 2017/2018. (5) There is an influence of school library utilization and learning independence simultaneously on the achievement of IPS student learning at SMP Negeri 4 Binamu Kabupaten Jeneponto Lesson Year 2017/2018.Â Keywords: Library Utilization, Learning Independence, Learning Achievement